1997
DOI: 10.1200/jco.1997.15.4.1553
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced tumor necrosis as a prognostic factor in localized Ewing's sarcoma of the extremities.

Abstract: The proposed histopathologic grading, to evaluate the effect of chemotherapy on the primary tumor, had the strongest correlation to clinical outcome. This method could therefore be used to identify patients with a high risk of recurrent disease. These patients could be randomized to receive alternative postoperative treatments to investigate whether more aggressive therapies will improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
167
1
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(182 citation statements)
references
References 21 publications
10
167
1
4
Order By: Relevance
“…Although the histologic response to initial chemotherapy was among the most reliable predictive factors, 16,17,28,31,32 even with the limitation that tumors had to be resected to determine response, we also used simple radiographic evaluations based on changes in extraosseous tumor size. These evaluations also demonstrated sufficient predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…Although the histologic response to initial chemotherapy was among the most reliable predictive factors, 16,17,28,31,32 even with the limitation that tumors had to be resected to determine response, we also used simple radiographic evaluations based on changes in extraosseous tumor size. These evaluations also demonstrated sufficient predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in patients with localised disease, poor histological response to chemotherapy (Picci et al, 1997;Bacci et al, 2000), tumour volume (Jürgens et al, 1988;Koscielniak et al, 1992;Ahrens et al, 1999), primary tumour site and age less than 15 years at diagnosis have been variably associated with adverse clinical outcome (Cotterill et al, 2000).…”
mentioning
confidence: 99%
“…An EFS of 70% was achieved for patients with localized disease, and OS reached 80%. [4][5][6][7][8][17][18][19][20][21] The outcome of metastatic patients remains dismal, especially for patients with bone and BM involvement. [4][5][6][9][10][11] Rodriguez Galindo et al 23 suggested risk stratification, taking into account simple clinical features, such as age, stage, tumor volume, localization and histological response to chemotherapy, to modulate treatment intensification in different subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In the past decade, ESFT outcome was improved largely through a multidisciplinary strategy based on surgery, radiotherapy and intensified chemotherapy regimens, [4][5][6] whereas large studies have identified risk factors associated with the worse prognosis. [4][5][6][7][8] Since the late 1980s, high-dose chemotherapy (HDC), followed by stem-cell rescue, has been proposed to improve the outcome of patients with poor-prognosis ESFT. Although many studies have been published, the role of HDC in ESFT remains unclear.…”
Section: Introductionmentioning
confidence: 99%